Impact of Financial Deregulation on Bank Productivity: Evidence from a Panel of Arab Banks (Journal of Asian Development Studies, 2013)
This paper investigates the effect of financial deregulation and liberalisation on the productivity growth and efficiency of eleven Arab banking sectors (6 GCC banking sectors and 5 non-GCC banking sectors) over the period 2000-2010. The Data Envelopment Analysis method and the Malmquist total factor productivity index are used to measure the productivity developments and to decompose it into: technical efficiency, technological change, scale efficiency, and total factor productivity. The empirical results show an overall improvement in technical efficiency of all Arab banking sectors under study. Conversely, we observe deterioration in technological and scale efficiencies for the majority of these banking systems over the studied period, which is translated into deterioration in overall productivity. We also find that whereas GCC banking sectors show stability in scale efficiency over the studied period, the non-GCC banking sectors recorded deterioration coupled with volatility in this measure. By comparing the two groups, we notice that GCC banks record on average higher technical and scale efficiency measures than non-GCC banks. Conversely, non-GCC banks record on average higher technological progress and total factor productivity measures. These results suggest that GCC banks have higher organisational and managerial efficiency and operate at the appropriate size. On the other hand, non-GCC banks have better ability to use technological advances in their production process.